Time Scales and Characteristics of Stock Markets in Different Investment Horizons - Mahata, Ajit; Nurujjaman, Md. (Frontiers in Physics, 2020)
Investors adopt varied investment strategies depending on the time scales ($τ$) of short-term and long-term investment time horizons ($ITH$). The nature of the market is very different in various investment $τ$. Empirical mode decomposition ($EMD$) based Hurst exponents ($H$) and normalized variance ($NV$) techniques have been applied to identify the $τ$ and characteristics of the market in different time horizons. The value of $H$ and $NV$ have been estimated for the decomposed intrinsic mode functions ($IMF$) of the stock price. We obtained $H_1=0.5±0.04$ and $H_1≥ 0.75$ for the $IMFs$ with $τ$ ranging from a few days to 3 months, and $τ≥$ 5 months, respectively. Based on the value of $H_1$, two time series have been reconstructed from the $IMFs$: (a) short-term time series [$X_{ST} (t)$] with $H_1=0.5± 0.04$ and $τ$ from a few days to 3 months; (b) long-term time series [$X_{LT} (t)$] with $H_1≥0.75$ and $τ≥$ 5 months. The $X_{ST}(t)$ and $X_{LT} (t)$ show that market dynamics is random in short-term $ITH$ and correlated in long-term $ITH$. We have also found that the $NV$ is very small in the short-term ITH and gradually increases for long-term $ITH$. The results further show that the stock prices are correlated with the fundamental variables of the company in the long-term $ITH$. The finding may help the investors to design investment and trading strategies in both short-term and long-term investment horizons.